2016
DOI: 10.1016/j.bbabio.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Water exit pathways and proton pumping mechanism in B-type cytochrome c oxidase from molecular dynamics simulations

Abstract: Cytochrome c oxidase (CcO) is a vital enzyme that catalyzes the reduction of molecular oxygen to water and pumps protons across mitochondrial and bacterial membranes. While proton uptake channels as well as water exit channels have been identified for A-type CcOs, the means by which water and protons exit B-type CcOs remain unclear. In this work, we investigate potential mechanisms for proton transport above the dinuclear center (DNC) in ba3-type CcO of Thermus thermophilus. Using long-time scale, all-atom mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 98 publications
5
45
0
Order By: Relevance
“…The CcO model that was employed for molecular dynamics simulations in Ref. [1] is based on the high resolution (1.8 Å) X-ray crystal structure of the ba 3 -type CcO from Thermus thermophilus in the reduced state in lipidic cubic phase (LCP) crystal as obtained from the Protein Data Bank (PDB: 3S8F ) [2] . This crystal structure contains two oxygen atoms between the Fe and Cu centers of the DNC, which have been proposed to be a bridging hydroperoxide [3] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CcO model that was employed for molecular dynamics simulations in Ref. [1] is based on the high resolution (1.8 Å) X-ray crystal structure of the ba 3 -type CcO from Thermus thermophilus in the reduced state in lipidic cubic phase (LCP) crystal as obtained from the Protein Data Bank (PDB: 3S8F ) [2] . This crystal structure contains two oxygen atoms between the Fe and Cu centers of the DNC, which have been proposed to be a bridging hydroperoxide [3] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The data provided in this article were generated for molecular dynamics (MD) simulations of ba 3 -type cytochrome c oxidase (CcO) of Thermus thermophilus [1] . Atomic coordinate data of cluster models of CcO cofactors are provided in XYZ coordinate format and atomic coordinate data of the entire CcO model embedded in POPC lipid bilayer and solvated with TIP3P water molecules and counterions are provided in PDB file format.…”
Section: Datamentioning
confidence: 99%
“…Based on the site-direct mutagenesis it is concluded that in the B type cytochrome oxidases, there is only one functioning entry channel for the uptake of both scalar and vectorial protons, the K-channel (154). For the proton transfer above the BNC of the ba 3 oxidase from T. thermophilus, a potential mechanism is proposed which involves the A propionate of heme a 3 , and the D372, H376, and E126 residues (155).…”
Section: Substrate-transfer Pathways: Protons O 2 H 2 Omentioning
confidence: 99%
“…The computational study suggests that the PLS is a cluster rather than a single residue (307) consisting of the A and D propionates of heme a 3 and nearby residues (e.g. Asp 52 and Lys171 © 1996-2017 in the bovine COX) (155). For the B family member, the ba 3 -type cytochrome oxidase, theoretical analysis suggests that the proton transfer above the BNC involves the A-propionate of heme a 3 and D372, H376 and E126 residues, with the H376 residue acting as the PLS (155) The exact path of the pumped proton above the E286 residue is not known.…”
Section: Models Of Proton-pumping Mechanism In Heme-copper Oxidasesmentioning
confidence: 99%
See 1 more Smart Citation